Theoretical and Legal Aspects of the Reclamation of Property from Unlawfull Possesion - M. V. Tregubov (Теоретическая и прикладная юриспруденция)
The article is devoted to the consideration of such issues as the permissibility of applying astrent to vindication claims, the possibility of vindication of property that is not expressed in material form. The focus is on studying the prospects of vindication claims in relation to such a new object of economic relations as cryptocurrency. Using formal-logical, retrospective methods, as well as the method of legal constructions, the author first studies the problem of applying a court penalty under the rules of art. 308.3 of the civil code of the Russian Federation (structurally located in the section on binding rights) to a real-law claim-vindicatson claim; secondly, it analyzes the evolution of scientific views on the permissibility of extrapolating real rights to intangible objects, including those that exist in a virtual environment. It is concluded that the question of the legality of awarding an astrent by a decision to satisfy a vindication claim is not clear in doctrinal terms, but judicial practice, in General, considers this issue positively; currently, Russian science is actively trying to determine the place of digital objects in the field of legal regulation. there are no fundamental obstacles to extrapolating the existing practice of the vindication analogy to the sphere of turnover of digital assets and values.